2019
DOI: 10.1101/772954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous retroviruses are a source of enhancers with oncogenic potential in acute myeloid leukaemia

Abstract: Endogenous retroviruses (ERVs) and other transposons can act as tissue-specific regulators of gene expression in cis, with potential to affect biological processes. In cancer, epigenetic alterations and transcription factor misregulation may uncover the regulatory potential of typically repressed ERVs, which could contribute to tumour evolution and progression. Here, we asked whether transposons help to rewire oncogenic transcriptional circuits in acute myeloid leukemia (AML). Using epigenomic data from both p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 68 publications
3
45
0
Order By: Relevance
“…Our work expands the TE expression-based perspective to a role of accessible TEs as cis-regulatory elements. Among the TE subfamilies accessible in LSCs, for example, we observed the LTR12C subfamily, whose elements work as enhancers in AML 34 and were previously shown to act as alternative promoters in hepatocellular carcinoma 71 . We further show that accessible TEs provide docking sites for oncogenic transcription regulators in LSCs.…”
Section: Discussionmentioning
confidence: 79%
“…Our work expands the TE expression-based perspective to a role of accessible TEs as cis-regulatory elements. Among the TE subfamilies accessible in LSCs, for example, we observed the LTR12C subfamily, whose elements work as enhancers in AML 34 and were previously shown to act as alternative promoters in hepatocellular carcinoma 71 . We further show that accessible TEs provide docking sites for oncogenic transcription regulators in LSCs.…”
Section: Discussionmentioning
confidence: 79%
“…Notably, it has also been reported that infection by Epstein-Barr Virus can lead to the activation of LTRs, such as ERV1 and ERVL, in the context of primary B-cells and lymphoblastoid cell lines [ 126 ]. New examples of LTRs functioning as enhancers to disease-relevant genes have recently been discovered for acute myeloid leukaemia [ 127 ]. Cancers are not only associated with upregulation of ERV regulatory elements but also the production of exapted TE-derived proteins that regulate the immune response [ 128 ].…”
Section: Gene Regulation By Transposable Elements: the Uglymentioning
confidence: 99%
“…Other LTR elements are also enriched in STAT1 binding sites (MLT1L) [14], or have been shown to act as cellular gene enhancers (LTR13A [16,31]).…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%